Violência na universidade: uma análise reflexiva nas perspectivas teórica e prático-pedagógica no contexto da UESPI em Parnaíba-PI - Nascimento, Maria do Rosário Pessoa (2014)
This doctoral dissertation has as its research object violence in the university. It is delimited by a theoretical and practical-reflective analysis in the context of the State University of Piauí UESPI, in the city of Parnaíba-PI. In the current stage of Modernity the social segments family, work, leisure, school present themselves as ever more demanding. In the University it is probable that the demand for new knowledge can contribute to conflicts arising between faculty and students creating a need to adapt conventional teaching to new educational paradigms. In this context this research paper has as its goal to analyze the probable factors which motivate violence in the university, its distinct forms of manifestation, pedagogical methods and the possible forms of overcoming. Specifically one hopes to: carry out theoretical studies about the University based on conceptual aspects, its origin and its historical trajectory, as well as its experience in the Brazilian reality; analyze the lack of association between research, knowledge and information; come to know the demands for the teaching practice and the changes proposed by the University Reform, considering the LDB/1996 and the National Plans foreseen for education; comprehend the ease of access and delineate the university student profile as to gender, as well as to academic, financial and family aspects; investigate the theme of violence in its conceptual aspects, its connection to lack of discipline, its historical and political context, and identify its characteristics based on the location where it takes place, including the university; identify the ways in which violence manifests itself based on physical or psychological traditional models, observing peculiarities of symbolic violence and of non-violence; verify the relation between violence and the school as a student environment, particularly in the university and discuss the polemical theory about the university initiation practical jokes play X violence; show the relevance of some social segments in university formation, considering the role of the family and education for citizenship as factors which can contribute to inhibiting violence; carry out field research aiming to identify, based on the data collected, the possible factors which induce violence in the university environment, especially at UESPI in Parnaíba-PI. The research stems from the following problem: what are the causes of violence, forms of expression, pedagogical methods utilized and measures to be taken by the HLI (Higher Learning Institution) which aim at inhibiting violent conduct? And how could the university education contribute to the development of the human person and of society so as to be less susceptible to the practice of violence and what are possible ways of overcoming? The research was based on the studies of various theoreticians, such as Carolina Imura, Cecília Minayo, Cipriano Luckesi, Danilo Streck, Dirceu Benincá, Hanna Arendt, Hélgio Trindade, Jackes Derrida, Marilena Chauí, Markus Brauer, Moacir Gadotti, Nilo Odália, Paulo Freire, Pierre Bourdieu, among others. The methodology adopted was based on a quali-quantitative approach with the presentation of statistics graphics based on the data collected. The research concludes that, based on the analysis of the data, the possibility of a pacific relationship in the university demands from the professors continuous formation, review of pedagogical methods and that, with a careful look, they seek to understand the social reality which involves the current educational policies and the personal relations which occurr in the university environment.